Two-stage synergy of electronic energy loss with defects in LiTaO3 under ion irradiation. Issue 6 (3rd June 2018) - Sellami, Neila; Crespillo, Miguel L.; Zhang, Yanwen; Weber, William J.
ABSTRACT: Understanding energy dissipation in electronic and atomic subsystems and subsequent defect evolution is a scientific challenge. Separate and combined effects of electronic and nuclear energy deposition in z-cut LiTaO3 have been investigated. Irradiation of pristine LiTaO3 samples with 2 MeV Ta ions leads to amorphization due to atomic displacement damage, described by a disorder accumulation model. While 21 MeV Si ions do not produce significant damage in pristine LiTaO3, introduction of pre-existing defects sensitizes LiTaO3 to the formation of ion tracks from the electronic energy loss by 21 MeV Si ions that induce a synergistic two-stage phase transition process. Impact statement Experimental study shows that the introduction of pre-existing defects prior to high energy irradiation sensitizes LiTaO3 to ion track formation leading to a synergistic two-stage phase transition process. GRAPHICAL ABSTRACT: